2021
DOI: 10.1038/s41598-021-81070-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabis on visual function and self-perceived visual quality

Abstract: Cannabis is one of the most used drugs of abuse in the world. The objective of this study was to analyze the effects of smoking cannabis on vision and to relate these to those perceived by the user. Thirty-one cannabis users participated in this study. Visual function assessment was carried out in a baseline session as well as after smoking cannabis. We evaluated static visual acuity, contrast sensitivity, stereoacuity, accommodative response, straylight, night-vision disturbances (halos) and pupil size. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
5
13
1
Order By: Relevance
“…Contrary to the other visual functions analyzed in this work, and considering published studies, there is no agreement as to whether alcohol consumption affects stereopsis, although some authors have found that this deteriorates under the effect of other drugs, such as cannabis [50,51]. According to our results, it is clear that both near and distance stereopsis are highly impaired under the effects of alcohol.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the other visual functions analyzed in this work, and considering published studies, there is no agreement as to whether alcohol consumption affects stereopsis, although some authors have found that this deteriorates under the effect of other drugs, such as cannabis [50,51]. According to our results, it is clear that both near and distance stereopsis are highly impaired under the effects of alcohol.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the pupil is also innervated by parasympathetic and sympathetic fibres, we did not find any significant changes in pupil size after cannabis use. This result is consistent with some previous findings, 23 although contradictory results have been published in the literature with regard to the effect of cannabis on pupil size 59,60 …”
Section: Discussionsupporting
confidence: 93%
“…Cannabis use also seems to alter accommodative function during the steady‐state response, since we found an increased accommodative lag for both target distances, even though this effect was not significant ( p = 0.08). Accommodative lags were similar to those found by a recent study in 31 young cannabis users for the baseline session and after smoking cannabis, although in that study cannabis use generated greater increase in the accommodative lag than in the present work 23 . In general, the lags observed here were comparable to those reported in recent studies employing the same optometer, although those works were not related to cannabis consumption 46,50,52,54 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations